Carbon Doping Triggered Efficient Electrochemical Hydrogen Evolution of Cross‐Linked Porous Ru‐MoO2 Via Solid‐Phase Reaction Strategy. Issue 1 (28th June 2022) - Cai, Jialin; Yang, Jianye; Xie, Xin; Ding, Jie; Liu, Leyan; Tian, Wanyu; Liu, Yushan; Tang, Zhiyong; Liu, Baozhong; Lu, Siyu
Abstract : The defect‐free structure of Mo‐based materials is a "double‐edged sword", which endows the material with excellent stability, but limits its chemical versatility and application in electrochemical hydrogen evolution reaction (HER). Carbon doping engineering is an attractive strategy to effectively improve the performance of Mo‐based catalyst and maintain their stability. Herein, we report a cross‐linked porous carbon‐doped MoO2 (C–MoO2 )‐based catalyst Ru/C–MoO2 for electrochemical HER, which is prepared by the convenient redox solid‐phase reaction (SPR) of porous RuO2 /Mo2 C composite precursor. Theoretical studies reveal that due to the presence of carbon atoms, the electronic structure of C–MoO2 has been properly adjusted, and the loaded small Ru nanoparticles provide a fast water dissociation rate and moderate H adsorption strength. In electrochemical studies under a pH‐universal environment, Ru/C–MoO2 electrocatalyst exhibits a low overpotential at a current density of 10 mA cm −2 and has a low Tafel slope. Meanwhile, Ru/C‐MoO2 has excellent stability for more than 100 h at an initial current density of 100 mA cm −2 . Abstract : In this article, a unique porous Ru/C–MoO2 electrocatalyst was successfully prepared through a well‐designed solid‐phase reaction strategy. Carbon doping improves the activity of initiating water dissociation, significantly reducing the energy barrier of the Tafel step, while the uniformly dispersed high active Ru acts as an effective catalytic center. Due to the special structure, Ru/C–MoO2 exhibits excellent catalytic activity and stability toward electrochemical hydrogen generation.